Transforming project management : an essential paradigm for turning your strategic planning into action - Petersen, Duane (Business professional collection, 2021)
"Turn your strategic-planning dreams into business reality with these project management and leadership best practices Executing on strategic planning is one of the biggest challenges leaders today. For example, Harvard Business Review reports that IT project failure costs businesses $3 trillion dollars annually. Stop Strategic Planning into the Abyss provides business leaders the key to addressing this issue head on. Stop Strategic Planning into the Abyss takes you beyond envisioning a great strategy and into the realm of implementing it-with skill, care, and expertise. Strategy-execution guru Duane Petersen reveals his unique and proven approach for tying strategic planning directly to project management. He explains how to break down a strategic plan into key objectives and project portfolios to make sense of all the project "parts," then successfully lead the execution of the plan. You'll learn how to evaluate where you are versus where you want to be, develop plans to move your vision forward, translate strategic plans into action plans with tangible efforts, budgets, and schedules, and guide and inspire the individuals and teams tasked with implementing their plans"--